Women of drama between theoretical and practical - علي عبد المحسن (College of Education for Women, 2019)
Greek theatre and roman theatre don't let for woman with working in the theatre such as writer , directing and acting theatre , so appear term women theatre in past sixty central because the woman feeling with iniquitousness in your life , so this search included several sections that include money parts . Part one is term theatre women. Part two causes show the women theatre. Part three jenouse women in writer, direction, and action in the world. Part four jenouse women in the Arab theatre. Part fife Iraqi woman jenouse in the theatre. Section tow includes analyses for once performance Iraqi theatre that include several women. This performance from editor and direction by kaseem - Muhammad, assistant in the direction montaha - rahem . that performance working in it several actors and actress , there are working the national grub for action. Section three results the search and discuses it.